Cortical aging – new insights with multiparametric quantitative MRI - Seiler, Alexander; Schöngrundner, Sophie; Stock, Benjamin; Nöth, Ulrike; Hattingen, Elke; Steinmetz, Helmuth; Klein, Johannes C.; Baudrexel, Simon; Wagner, Marlies; Deichmann, Ralf; Gracien, René-Maxime (Aging (Albany, NY.), 2020)
Understanding the microstructural changes related to physiological aging of the cerebral cortex is pivotal to differentiate healthy aging from neurodegenerative processes. The aim of this study was to investigate the age-related global changes of cortical microstructure and regional patterns using multiparametric quantitative MRI (qMRI) in healthy subjects with a wide age range. 40 healthy participants (age range: 2 to 8 decade) underwent high-resolution qMRI including T1, PD as well as T2, T2* and T2' mapping at 3 Tesla. Cortical reconstruction was performed with the FreeSurfer toolbox, followed by tests for correlations between qMRI parameters and age. Cortical T1 values were negatively correlated with age (p=0.007) and there was a widespread age-related decrease of cortical T1 involving the frontal and the parietotemporal cortex, while T2 was correlated positively with age, both in frontoparietal areas and globally (p=0.004). Cortical T2' values showed the most widespread associations across the cortex and strongest correlation with age (r= -0.724, p=0.0001). PD and T2* did not correlate with age. Multiparametric qMRI allows to characterize cortical aging, unveiling parameter-specific patterns. Quantitative T2' mapping seems to be a promising imaging biomarker of cortical age-related changes, suggesting that global cortical iron deposition is a prominent process in healthy aging.